Prospects Of Molybdenum Thin Film For Solar Cell Application From AFM Analysis - Arith, Faiz; Amin, Nowshad; Chelvanathan, Puvaneswaran; Idris, Muhammad Idzdihar (AENSI Journals, 2014)
Molybdenum (Mo) was grown on soda lime glass by the radio frequency (RF) magnetron sputtering deposition method to characterize the prospect feature to be used as solar cell back contact. 10 samples were sputtered with different suitable parameter by varying RF target power, argon gas pressure and growth temperature. Then all the samples were analyzed by atomic force microscopy (AFM) to determine their features and specification. The results include molybdenum thin film characteristics of roughness, grain size and root mean square (RMS) is obtained. From these characterization results the paramount parameter condition is obtained which at 200 °C, 6.6 mTorr and 75 Watt. These optimized results can be used in future work for fabricating of molybdenum as back contact layer for solar cell application. In conclusion, this study has obtained the optimized parameter in term of growth temperature, argon (Ar) gas pressure and radio frequency (RF) power for molybdenum growth on thin films that compatible and can be integrated not only for solar cell application but with wide variety of MEMS/NEMS devices.